ADVANTAGES OF USING INTERACTIVE METHODS IN THE DEVELOPMENT OF CREATIVE THINKING ABILITY OF 5-6 YEAR OLD CHILDREN - Bobojonova, Muyassar Obodovna (SCIENCE and SOCIETY, 2026)
This article discusses the advantages and features of using interactive methods in developing the creative thinking abilities of 5-6 year old children.
Keywords: education; thinking; creative thinking; preschool age; first step; state requirements; developmental environment